Creación de un bróker de pequeños productores de artículos de cuero del sector de Quisapincha provincia de Tungurahua con perspectivas de exportación a Chile - Cevallos Maldonado, Adriana Cristina (2014)
The purpose of this research is to create a broker for publishing the textile market by the manufacturing of leather goods (shoes, purses and jackets) because of the national and international commerce of this economic sector has not taken advantage as it should be. With this premise our purpose is to benefit to various sectors, among the most important are the Quisapinchas artisan, in the same way we want to distinguish this canton as the principal manufacturing textile leather manufactory with a gradual positioning of Ecuadorians brands in the international market. Actually around the 80% of Quisapinchas population relates direct and indirect between manufactory and commerce of leather goods focusing on the products that will be presented to international market by creating the “Leather Fashion” broker.